SISTEM INFORMASI GEOGRAFIS CLUSTERISASI VAKSINASI DI KECAMATAN LOWOKWARU (MALANG) MENGGUNAKAN K-MEANS - Abshor Naufar Hakim; Febry Eka Purwiantono (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
Abstract Lowokwaru Malang District is one of the many sub-districts in East Java. This sub-district is located in Malang City and has 12 villages or sub-districts. Some of the residents did not know information on the development of vaccinations in Lowokwaru District so that some residents felt uncomfortable if there were residents who had not vaccinated to prevent the spread of COVID-19. Especially newcomers from outside who do not know about vaccination developments in the Lowokwaru sub-district. So we need a geographic information system that can provide information about the spread of vaccinations in the District of Lowokwaru Malang. So we need a website that can be used to see how the conditions for the spread of vaccinations in Lowokwaru District are using the k-means method. The results of the trial will show the condition of each area of Lowokwaru Malang District which is marked with red zones (vaccination distribution is still lacking), yellow (vaccination distribution is quite good), and green (vaccination distribution is almost maximal). And these results will be entered into the system.